Effect of hygrothermal cycles on mechanical performance of composite adhesively bonded joints - Rincon Urbina, Sonia; Ayre, David; Yazdani Nezhad, Hamed (European Society for Composite Materials, 2018)
This paper numerically and experimentally studied mechanical performance of composite adhesively bonded single-lap joints in the presence of hygrothermal cycles, under static tensile loading. Joint performance was predicted by the development of a coupled experimental-numerical approach based on cohesive zone modelling. Composite adherends of aerospace grade carbon fibre-reinforced Hexply® M21/T800 pre-impregnated plies, bonded using a 25mm × 25mm bond overlap. Bond interface was exposed to cyclic moisture and temperature loads by introduction of 2mm sharp cracks at joint runouts. Pre-cracked joint specimens were subjected to hygrothermal cycles in environmental chamber under conditions representative of aircraft operational cycles. Testing proved that joint degradation occurred with increased cycle numbers. Strength reduced by 42% under static load after 714 cycles compared to unaged joints. Degradation accelerated in the initial 84 cycles, but was reduced for higher cycles attributed to adhesive bulk moisture saturation. Moisture diffusion parameters were characterised for both adhesive and composite subjected to hygrothermal cycles. Adhesive reached moisture saturation level of 1.54%wt, while composite laminate was 0.68%wt. In both cases, moisture diffusion followed Fick's second law. Displacement-diffusion analysis determined effect of moisture on elasticity of adhesive. This analysis plus the single-lap test data were coupled to develop degradation parameters required for CZM, demonstrating an 87% accuracy at 714 hygrothermal cycles.
Keywords: Hygrothermal cyclic ageing; adhesive joints; mechanical testing; finite element analysis